Leadership Patterns and their Impact on Organizational Behaviour at Tikrit University - Hassan F. Ahmed (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The purpose of this study is to explore the role of leadership models on organizational behavior at the University of Tikrit as they positively affect organizational behavior. The study sample consisted of 180 employees at the University of Tikrit, and Use descriptive analysis methods. A questionnaire was used as a tool for research and data collection, and the statistical program SPSS was used to analyze the research questionnaire. The study found that leadership models and their impact on organizational behavior have statistically significant effects at the significant level (0.05). The researcher explained that leadership styles play Plays a vital role in improving employee organizational behavior at Tikrit University and thus contribute to improving the university's performance and enhancing students' academic achievement.